Educação em tempos de desenvolvimentismo:: o discurso em torno da formação para o trabalho nos Ginásios de Pernambuco (1969-1971) (Revista de História Regional, 2022)
This work aims to analyze the narratives around the Work Oriented gymnasiums in Pernambuco, between 1969 and 1971. From the study of publications in the Official Diary, as well as the Pernambuco daily newspaper, we seek to problematize the discourses of the local political class. The results show that local agents did not fully adhere to the national project, but alternated between moments of adherence and detachment with regard to strategies to legitimize training for work in these gymnasiums.